7×2-14=49

Add 14 to both sides of the equation.

7×2=49+14

Add 49 and 14.

7×2=63

7×2=63

Divide each term in 7×2=63 by 7.

7×27=637

Cancel the common factor of 7.

Cancel the common factor.

7×27=637

Divide x2 by 1.

x2=637

x2=637

Divide 63 by 7.

x2=9

x2=9

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±9

Simplify the right side of the equation.

Rewrite 9 as 32.

x=±32

Pull terms out from under the radical, assuming positive real numbers.

x=±3

x=±3

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=3

Next, use the negative value of the ± to find the second solution.

x=-3

The complete solution is the result of both the positive and negative portions of the solution.

x=3,-3

x=3,-3

x=3,-3

Solve Using the Square Root Property 7x^2-14=49